Early Introduction of Solid Feeds: Ingestion Level Matters More Than Prebiotic Supplementation for Shaping Gut Microbiota - Paës, Charlotte; Gidenne, Thierry; Bébin, Karine; Duperray, Joël; Gohier, Charly; Guené-Grand, Emeline; Rebours, Gwénaël; Bouchez, Olivier; Barilly, Céline; Aymard, Patrick; Combes, Sylvie (Frontiers in Veterinary Science, 2020)
Early introduction of a nutritional substrate is a promising biomimetic strategy for controlling the implantation of the microbiota and preserving the health of young animals. In this study, we provided experimental solid substrate in a gel form to stimulate suckling rabbits' intake and to investigate its effects on microbiota implantation and colonization. All the rabbits had access to solid feed outside the nest as of 15 days of age. Except for the control group, rabbits were offered starter feed gels inside the nests from 3 to 18 days of age. These gels were either free of additives (AF_GEL) or contained 4% of fructo-oligosaccharides (FOS_GEL) or 4% of mannan-oligosaccharides and β-glucans mixtures (MOS_GEL). The cecal content of 160 rabbits was sampled at 18, 29, 38, and 57 days of age and analyzed using 16S rRNA gene sequencing. Pups consumed an average of 3.95 ± 1.07 g of starter feed gel with a higher intake when it was supplemented with fructo-oligosaccharides (+1.2 g; P < 0.05). Starter feed gel consumption increased the ensuing intake of pellets (+17 g from 15 to 21 days; P < 0.05). Alpha-diversity indexes were similar between groups and prebiotic supplementation did not induce a clear shift in microbiota pattern. Conversely, when considering rabbits that consumed more starter feed, the highest proportions of bacteria with plant-degrading abilities, such as species from the Lachnospiraceae and Ruminococcaceae families, were observed at 18 days of age. However, fermentative activities were not affected by starter feed intake at 29, 38, and 57 days of age. By providing comprehensive results on the regulation of microbial community structure at the onset of solid feed intake, this research paves the way for further studies on digestive ecosystem maturation.